EVALUATION OF THE EXPECTATION–EXPERIENCE GAP AND INFORMATION TRANSPARENCY ON PATIENT SATISFACTION - Dini Indriani; Kosasih (RADJA PUBLIKA, 2026)
Patient satisfaction is a key indicator in evaluating the quality of healthcare services, particularly in the context of patient-centered care. This study aims to analyze the impact of the expectation–experience gap and information transparency on patient satisfaction through a literature review approach. The expectation–experience gap refers to the discrepancy between patients’ prior expectations and their actual experiences during healthcare service delivery, while information transparency relates to the clarity, openness, and accessibility of information provided to patients. This study employs a qualitative literature review method by collecting and analyzing secondary data from peer-reviewed journals, books, and relevant academic sources. The selected literature focuses on healthcare service quality, patient satisfaction, and communication practices. The analysis is conducted using a thematic approach to identify patterns, relationships, and key findings related to the research variables. The results indicate that the expectation–experience gap has a direct and significant effect on patient satisfaction. A smaller gap leads to higher satisfaction, while a larger gap results in dissatisfaction.